The alterations of immunological reactivity in heroin addicts and their normalization in patients maintained on methadone - Zajícová, A; Wilczek, H; Holán, V (Folia biologica, 2004)
Drug addiction influences many physiological functions including reactions of the immune system. The higher occurence of infectious and other diseases in drug addicts has been explained by the depression of immunity due to the harmful effects of the drug. To test this assumption, we tested the proliferative responsiveness and cytokine production of PBL from a group of heroin addicts (N = 19), patients maintained on methadone (N = 15) and healthy controls (N=15). The results show that Con A-induced proliferation of PBL from heroin addicts was even enhanced in comparison with PBL from the control group. Similarly, production of IL-2, IL-10 and IFNgamma was higher in the group of heroin addicts than in healthy controls. The enhanced proliferation of PBL or the increased production of cytokines observed in heroin addicts was partially or completely normalized in the group of patients maintained on methadone. A significantly higher production of IL-6 was found in both unstimulated and stimulated PBL from heroin addicts and patients maintained on methadone, when compared with PBL from healthy controls. The results thus showed enhanced proliferative activity and increased production of various cytokines in heroin addicts and partial or complete adjustment of these alterations in patients maintained on methadone.
Keywords: závislost na heroinu; Heroin Dependence; cytokiny; Female; Adult; dospělí; Humans; ženské pohlaví; mužské pohlaví; Concanavalin A; lidé; Male; methadon; Leukocytes; Methadone; leukocyty; Cytokines; konkanavalin A